Numerical investigation of blood flow effects on temperature distribution in pulmonary tumors during magnetic induction hyperthermia - Liu, Xiao; Lu, Mai (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMagnetic Induction Hyperthermia (MIH) has emerged as a promising physical approach for tumor treatment and has attracted increasing attention in clinical research. However, most existing studies primarily focus on optimizing magnetic nanoparticle properties and magnetic field parameters, while the heat sink effects induced by blood flow within the treatment region remain insufficiently explored.MethodsIn this study, a three-dimensional lung tumor model incorporating vascular structures and laminar blood flow was established based on multiphysics coupling theory. Using the COMSOL Multiphysics finite element platform, the coupled magnetic, electric, and thermal fields during MIH treatment were simulated to analyze the influence of blood flow on temperature distribution.ResultsSimulation results demonstrated that, without blood flow, the tumor center temperature rapidly increased to 47.7 °C within 300 s, and the peripheral temperature remained above 42 °C, achieving effective hyperthermia. In contrast, when blood flow was introduced, the heat sink effect significantly reduced the therapeutic temperature—the tumor center dropped to 44.5 °C, and the minimum peripheral temperature decreased to 39.4 °C. Both blood flow velocity and vessel diameter were found to strongly influence the heat sink , with lower flow velocity or smaller vessel diameter will mitigate the effect.DiscussionThis study suggests that temperature uniformity during magnetic induction hyperthermia (MIH) can be improved by increasing the number of Helmholtz coil turns, enhancing the excitation current, or optimizing the distribution of magnetic fluid within the tumor region. These findings provide theoretical insights into the role of blood flow in MIH and offer practical guidance for individualized clinical treatment planning.